A Coherently Strained Monoclinic [111]PbTiO3 Film Exhibiting Zero Poisson's Ratio State. (20th June 2019) - Tang, Yunlong; Zhu, Yinlian; Ma, Xiuliang; Hong, Zijian; Wang, Yujia; Wang, Wenyuan; Xu, Yaobin; Liu, Ying; Wu, Bo; Chen, Lang; Huang, Chuanwei; Chen, Longqing; et al.
Abstract: [111]‐Oriented perovskite oxide films exhibit unique interfacial and symmetry breaking effects, which are promising for novel quantum materials as topological insulators and polar metals. However, due to strong polar mismatch and complex structural reconstructions on (111) surfaces/interfaces, it is still challenging to grow high quality [111] perovskite heterostructures, let alone explore the as‐resultant physical properties. Here, the fabrication of ultrathin PbTiO3 films grown on a SrTiO3 (111) substrate with atomically defined surfaces, by pulsed laser deposition, is reported. High‐resolution scanning transmission electron microscopy and X‐ray diffraction reveal that the as‐grown [111]PbTiO3 films are coherent with the substrate and compressively strained along all in‐plane directions. In contrast, the out‐of‐plane lattices are almost unchanged compared with that of bulk PbTiO3, resulting in a 4% contraction in unit cell volume and a nearly zero Poisson's ratio. Ferroelectric displacement mapping reveals a monoclinic distortion within the compressed [111]PbTiO3, with a polarization larger than 50 µC cm −2 . The present findings, as further corroborated by phase field simulations and first principle calculations, differ significantly from the common [001]‐oriented films. Fabricating oxide films through [111] epitaxy may facilitate the formation of new phase components and exploration of novel physical properties for future electronic nanodevices. Abstract : Monoclinic [111]PbTiO3 ultrathin films exhibit an extreme Poisson's ratio. Atomically defined, monoclinic and polar [111]PbTiO3 ultrathin films exhibiting extreme Poisson's ratios are obtained. Polar mismatch and structural reconstructions on (111) perovskite surfaces/interfaces pose a substantial challenge for preparing (111) films. Herein, novel phase components and special strain states are achieved through [111] epitaxial growth of PbTiO3 films.